Ant sharing by plant species bearing extrafloral nectaries has a low impact on plant herbivory in a tropical system - Souza, Caroline; Leal, Laura C.; Baccaro, Fabrício B.; Bergamo, Pedro J. [UNESP]; Bronstein, Judith L.; Rey, Pedro J.; Nogueira, Anselmo (Wiley, 2024)
Plant species bearing extrafloral nectaries (EFNs) may indirectly influence other plant species by sharing protective ants, potentially altering herbivory levels. However, the propagation of indirect effects in this type of mutualism has seldom been investigated. We investigated indirect effects via ant sharing among 21 EFN-bearing plant species of the tribe Bignonieae distributed on 28 plots in the central Brazilian Amazon. We used an ecological network index to quantify potential indirect effects among plant species through shared dominant and subordinate ant species. Plant species that were more attractive to ants (promoter species) had the highest potential to indirectly influence ant visitation to less attractive plant species (receptor species) in the community, primarily through changes in the attraction of dominant ant species. However, these potential indirect effects did not result in significant differences in herbivory patterns among the studied plants. Ant attendance and herbivory levels were similar among promoter species, neighbouring plants, and non-neighbouring plants. Unlike other mutualisms involving plants (e.g., pollination), the indirect effects among plant species that share protective ants had limited consequences. The low levels of herbivory and the small foraging areas of shared ant defenders could be responsible for the observed limited impact of indirect interactions among plant species in this system. Synthesis: This study demonstrates that plant species with EFNs can indirectly influence other plant species through ant sharing. The attractiveness of certain plants to ants enables them to affect the ant visitation patterns of less attractive plants in the community. However, these indirect effects did not significantly alter herbivory levels among plants. Overall, this study advances ecological understanding by showing that the sharing of protective ants among plant species can in some cases confer limited costs and benefits, leading indirect interactions to have minimal impact on herbivory patterns.
Keywords: ant–plant mutualism; competition; facilitation; herbivory; indirect interactions; mutualistic networks; Müller's index; protection